Rates of protein synthesis are maintained in brain but reduced in skeletal muscle during dietary sulfur amino acid restriction - Martinez, Wenceslao; Zhang, Qian; Linden, Melissa A.; Schacher, Nate; Darvish, Sanna; Mirek, Emily T.; Levy, Jordan L.; Jonsson, William O.; Anthony, Tracy G.; Hamilton, Karyn L. (Frontiers in Aging, 2022)
Dietary interventions such as sulfur amino acid restriction (SAAR) target multiple drivers of aging, and show promise for preventing or delaying the onset of chronic diseases. SAAR promotes metabolic health and longevity in laboratory animals. The effects of SAAR on proteostasis remain relatively unexplored. We previously reported that SAAR promotes mitochondrial proteostatic maintenance, despite suppression of global protein synthesis, in two peripheral tissues, the liver and skeletal muscle. However, the brain, a tissue vulnerable to age-related neurodegenerative diseases due to the loss of proteostasis, has not been thoroughly studied. Therefore, we sought to reveal proteostatic responses in the brains of mice fed SAAR for 35 days. Here, we demonstrate that male C57Bl/6J mice fed two levels of SAAR maintained rates of protein synthesis in all sub-cellular fractions of the pre-frontal cortex. In comparison, rates of skeletal muscle protein synthesis in SAAR fed mice were slower than control-fed mice. To gain mechanistic insight, we examined several key nutrient/energy sensitive signaling proteins: AMP-activated protein kinase (AMPK), eukaryotic initiation factor 2 (eIF2), and ribosomal protein S6 (rpS6). SAAR had minimal to modest effects on the total abundance and phosphorylation of these proteins in both tissues. Our results indicate that the pre-frontal cortex in brain is resistant to perturbations in protein synthesis in mice fed SAAR, unlike skeletal muscle, which had a reduction in global protein synthesis. The results from this study demonstrate that proteostatic control in brain is of higher priority than skeletal muscle during dietary SAAR.